Can Forests Endure the Energy Race and Ecological Pressures? A VAR Analysis of MINT Countries - Fazriyas, Fazriyas; Kurniadi, Anggi Putri; Basri, Elvy; Rasjid, Muhammad Rachmad (International Journal of Energy Economics and Policy, 2025)
This study investigates forest resilience in the face of intensifying energy competition and ecological pressures in MINT countries (Mexico, Indonesia, Nigeria, and Turkey) from 1990 to 2024. Energy competition is represented by renewable and non-renewable energy consumption, while ecological pressures are assessed through environmental degradation, green economic growth, and population density. Using a Vector Autoregression (VAR) approach, all variables are treated as endogenous to capture dynamic feedback relationships. Stationarity tests confirm that most variables are first- difference stationary without long-run cointegration. Granger causality analysis reveals bidirectional relationships between forest area (FA) and non-renewable energy consumption, and between environmental degradation and population density. Unidirectional causality is also found from renewable energy consumption, environmental degradation, and green economic growth to FA; from environmental degradation to renewable energy consumption; and from FA and non-renewable energy consumption to population density. Impulse response and variance decomposition results suggest that non-renewable energy consumption and ecological, such as environmental degradation and population density have a negative impact on FA, whereas renewable energy consumption and green economic growth contribute positively. The findings highlight the urgent need to integrate energy, environmental, and development policies to support forest sustainability amid growing global energy demands and ecological stress.